2021
DOI: 10.3389/fgwh.2021.761511
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Gender in COVID-19 Vaccine Research: Substantial Evidence Gaps Remain

Abstract: Since the start of the COVID-19 pandemic there has been a global call for sex/gender-disaggregated data to be made available, which has uncovered important findings about COVID-19 testing, incidence, severity, hospitalisations, and deaths. This mini review scopes the evidence base for efficacy, effectiveness, and safety of COVID-19 vaccines from both experimental and observational research, and asks whether (1) women and men were equally recruited and represented in vaccine research, (2) the outcomes of studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
44
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 73 publications
11
44
0
1
Order By: Relevance
“…Both sexes appear to be equally affected; no clear preponderance could be made out probably owing to the limited number of reports. Prior cohort studies and reviews have reported an association between female sex and adverse effects after COVID vaccination ( Beatty et al, 2021 , Vassallo et al, 2021 ); this has been explained by higher vaccine reactogenicity among women and the role of hormonal, microbiota, and genetic responses ( Venkatakrishnan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both sexes appear to be equally affected; no clear preponderance could be made out probably owing to the limited number of reports. Prior cohort studies and reviews have reported an association between female sex and adverse effects after COVID vaccination ( Beatty et al, 2021 , Vassallo et al, 2021 ); this has been explained by higher vaccine reactogenicity among women and the role of hormonal, microbiota, and genetic responses ( Venkatakrishnan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences in immune response have been explained by the hormonal milieu that can have profound effects on B-cell activity regulation, antibody production and vaccine efficacy, with an elevated level of estradiol associated with higher vaccine-induced immunity [32]. Current data on SARS-CoV-2 vaccination are not sufficient to draw definitive conclusions on sex differences in vaccine efficacy, as reported in a recent review of 41 experimental and observational studies in which Vassallo, A. et al explained the failure to recognize the gender difference through a lack of attention to sex/gender-specific evidence in the design of COVID-19 vaccine research [33].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study on the 75 clinical trials on different types of COVID-19 vaccines, 24% reported their main results disaggregated by gender, and only 13% mentioned the implications of their study for females and males [14]. In a mini review of studies reporting safety outcomes of COVID-19 vaccines, the authors found a significant lack of gender-disaggregated evidence across studies [15].…”
Section: Introductionmentioning
confidence: 99%